SU116. Longitudinal Epigenetic Analysis of Clozapine Use in Treatment-Resistant Schizophrenia - Gillespie, Amy (Schizophr Bull, 2017)
Background: Approximately one-third of patients with schizophrenia are considered treatment resistant. For these patients, the atypical antipsychotic drug clozapine is recommended as the only evidence-based treatment available. However, there is still significant variability in treatment response and many patients suffer side effects. Animal studies have demonstrated that clozapine influences histone modification and DNA methylation, and a recent EWAS study in humans identified multiple differentially methylated positions (DMPs) and differentially methylated regions (DMRs) in clozapine-exposed samples. In the current study, we used a longitudinal, within-participant design to conduct genome-wide analysis of DNA methylation changes in treatment-resistant patients over 6 months of clozapine use. Methods: We recruited 26 participants with a diagnosis of treatment-resistant schizophrenia, before they were prescribed clozapine. We then collected whole-blood samples at baseline and follow-up (6 or 8 wks, 12 wks, and 6 mo after clozapine start date), alongside clinical assessments. This included assessment of treatment response (defined as at least a 20% reduction in PANSS score) and side effects. We quantified DNA methylation at ~480 000 sites across the genome using the Illumina 450K HumanMethylation array and following preprocessing, normalization, and quality control; an epigenome-wide association study was performed comparing DNA methylation over the 4 time points. The trajectories of those with different treatment response/side effects will also be compared. Results: There was a reduction in overall global DNA methylation associated with length of time on clozapine, and multiple individual CpG sites show changes in DNA methylation that were found to be significantly associated with length of time exposed to clozapine. Numerous sites within the top twenty are located within the body of genes associated with immune system and antibodies. Conclusion: This is the first study to identify longitudinal epigenetic changes following clozapine exposure in human subjects. Recruitment and analysis are ongoing, with plans to compare DNA methylation between clozapine responders and nonresponders. Ultimately, these data will help us understand the mechanisms involved in clozapine, potentially providing biomarkers to predict response to clozapine.